The Hidden Benefits of the Salts of Life (Advancements in Homeopathic Research, 2022)
Human body during health break down food into organized material into its simpler constituents, amino acids, sugar, mineral elements, carbon, hydrogen etc as well as their absorption by the body tissues. The ceaseless activity of this complicated process constitutes the body’s metabolism. Disease invariably disturb the metabolism. A chemical change affects the blood for a good purpose and in all healing, this is a silent factor of great value.1 The Schussler tissue salts are inorganic mineral substance very same of which our earth and its soils are composed of. These substances are suitably selected and prepared and taken as remedies for various diseases or physically disturbances which are now known as tissue remedies.2
Keywords: Tissue salts; Infinitesimal; Homoeopathy; Trituration; Silicea